Pengaruh Disiplin Kerja, Keselamatan Kerja Dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan Pada PT VME Process - Prastyana, Widya Monica; Hikmah (LPPM Universitas Putera Batam, 2021)
The aim of this learning was to specify if an effect of work discipline, work safety and health on the work productivity of PT VME Process employees with a sample total of 180 respondents. The collection data method used a questionnaire which was distributed directly, the quality data test in this learn used validity and reliability tests, the classical hypothesis test and the leverage test were performed in this learning utilize multiple linear regression analysis and coefficient of determinaton (R2) analysis while for the hypothesis test on This learn uses (t test) and (f test) use the SPSS 25 software. coefficient of determination (R2) obtained from the labor discipline, occupational safety and health variables is 79.1% of the labor productivity variables. From the outcome of the t test and the f test, we can conclude from this study that there is a positive and significant leverage between the variables of work discipline, work safety and work health on work productivity, as well as a significant influence between the Three. independent variable which is a mutant of the dependent variable.